The Use of Reading Corners to Improve Students' Reading Literacy: Classroom Action Research at MI Yahya Bekasi - Heni Purningsih (MANDAILING GLOBAL EDUKASIA, 2025)
This classroom action research aims to explore the effectiveness of implementing a Reading Corner to improve reading literacy among students at MI Yahya Bekasi. The study was conducted over two cycles, each consisting of planning, implementation, observation, and reflection stages. The participants were 27 fourth-grade students selected through purposive sampling. The main objective was to enhance students’ reading interest, comprehension, and fluency through an engaging and student-centered reading environment. Quantitative and qualitative data were collected through observation sheets, reading comprehension tests, and student questionnaires. In the initial observation, only 41% of students demonstrated sufficient reading literacy. After the first cycle, the percentage increased to 63%, and by the end of the second cycle, it reached 85%. The improvement was observed in students’ ability to identify main ideas, infer meaning from context, and respond critically to texts. The use of the Reading Corner fostered a more positive reading habit, with students spending more time voluntarily reading both fiction and non-fiction texts. Qualitative findings indicated a shift in classroom atmosphere toward a more literate culture. Students reported increased motivation and enjoyment in reading activities. Teachers also noted improvements in student engagement and participation during reading sessions. The integration of visual aids, diverse reading materials, and reflective discussions within the Reading Corner contributed significantly to the overall literacy development.This study concludes that the implementation of a Reading Corner is an effective strategy to enhance reading literacy in elementary school settings. It provides an accessible, low-cost, and adaptable model that can be replicated in similar educational contexts. Future research is encouraged to examine long-term impacts and integrate digital literacy tools to complement physical reading environments.